2019
DOI: 10.17140/hroj-6-149
|View full text |Cite
|
Sign up to set email alerts
|

Changes on Electrocardiographic Patterns and Associated Factors among Chronic Obstructive Pulmonary Disease Patients

Abstract: Background Chronic obstructive pulmonary disease (COPD) is a preventable and treatable disease characterized by airflow limitation that is not fully reversible. The lungs and the heart are so closely interrelated organs that diseases of the one results in impaired functioning of the other. COPD induced cardiovascular diseases (CVDs) are diagnosed by electrocardiogram (ECG) and other instruments. ECG is one of the basic diagnostic tools that uses in early screening of COPD associated systemic effect of CVDs. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…21,22 The importance of conducting an ECG examination in performing cardiovascular disease management in COPD patients for a better patient prognosis. 23 In this study, the age of most COPD sufferers was ≥60 years old. As we age, the body's ability to regenerate will decrease, so damaged body cells will be replaced by fibrosis tissue.…”
Section: Discussionmentioning
confidence: 78%
“…21,22 The importance of conducting an ECG examination in performing cardiovascular disease management in COPD patients for a better patient prognosis. 23 In this study, the age of most COPD sufferers was ≥60 years old. As we age, the body's ability to regenerate will decrease, so damaged body cells will be replaced by fibrosis tissue.…”
Section: Discussionmentioning
confidence: 78%
“…Найбільш інформативним при ХОЗЛ у поєднанні з ІХС є метод добового моніторування ЕКГ. Це багато в чому пов'язано з тим, що при цьому методі пацієнти незалежно від застережень лікаря намагаються проявити найбільшу фізичну активність [37,38].…”
Section: іхс та хозл: спільні риси патогенезу складності діагностики та лікуванняunclassified
“…COPD is associated with specific electrocardiographic (ECG) abnormalities. Previous studies have reported that patients with COPD had a higher risk of myocardial infarction, cardiac arrhythmia, atrial fibrillation, non-sustained ventricular tachycardia, and sustained ventricular tachycardia [ 8 , 9 ]. International studies about acute COPD exacerbation have revealed that the frequency of a new ECG finding is high during exacerbation compared with baseline.…”
Section: Introductionmentioning
confidence: 99%